Formulasi dan Uji Aktivitas Sediaan Krim Sunscreen Ekstrak Daun Balangkasua (Lepisanthes alata (Blume) Lennh) (Journal of Tropical Pharmacy and Chemistry, 2026)
Balangkasua leaves (Lepisanthes alata (Blume) Leenh.) are known to contain secondary metabolites, particularlyphenolics and flavonoids, which have the potential to be used as active ingredients in natural sunscreens. This study aims to determine the content of secondary metabolites inbalangkasua leaf extract. To determine the physical characteristics and stability of the balangkasua leaf extract sunscreen cream formulation. To determine the SPF value of balangkasua leavesand balangkasua leaf extract sunscreen cream. To determine whether thebalangkasua leaf extract sunscreen formulation is safe and acceptable tousers based on the results of irritation and hedonic tests. In the phytochemical screening test, balangkasua leaf extract contained alkaloids, tannins, flavonoids, saponins, and steroids. The formulated sunscreen good physical stability, although in the fourth cycle there was a slightphase separation. The SPF values of balangkasua leaf extract at concentrations of 400 ppm, 600 ppm, and 800 ppm showed ultra protection of 20.21, 24.13, and 28.22, respectively. The SPF obtained from the three formulations of balangkasua leaf extract creamwere F1 15.37, F2 23.16, and F3 32.35, all of which fall into the “ultra” protection category. Based on the results of irritation, cream formulations demonstrated safe properties and were well-tolerated users.